Influence of Mother Tongue on English Language Learning in the EFL Context of Nepal - Raut, Bhakta Bahadur (GS WOW: Wisdom of Worthy Research Journal, 2024)
This article explores the influence of the mother tongue on English language learning in EFL classrooms in the Nepalese context. The study adopts a qualitative approach, gathering data through literature reviews and the author’s own teaching experiences and empirical observations in various English classes. The findings reveal that while mother tongue influence on target language learning is inevitable, excessive reliance on the mother tongue in EFL teaching can hinder students’ learning outcomes. The study emphasizes that all languages share certain similarities, which can be leveraged as tools for teaching English effectively. It suggests that a judicious use of the mother tongue is the most effective approach in Nepalese EFL classrooms. Additionally, the article highlights the potential of e-learning, drilling activities, songs and videos, and contextual teaching methods as effective tools to minimize the influence of the mother tongue in English language learning.